Short Communications : Microsatellite based association studies for grain mineral content in local winter (Sali) rice of Assam - Pathak, Khanin; Rathi, Sunayana; Verma, H.; Baishya, S.; Sarma, R.N. (The Indian Journal of Genetics and Plant Breeding, 2016)
In present investigation, grains of one hundred indica rice genotypes were analyzed for nine mineral contents namely, phosphorus (P), potassium (K), sodium (Na), magnesium (Mg), calcium (Ca), zinc (Zn), iron (Fe), manganese (Mn) and copper (Cu) and genotyped using 112 SSR markers. STRUCTURE analysis identified k=4, indicating at least four distinct groups in a set of 100 rice accessions. Genomewide scanning detected a total of 10 significant markertrait associations (P<0.01), with the R2 values ranging from 8.85% to 24.25%. Three markers, RM231 on chromosome (Chr.) 3, RM234 (chr. 7) and RM162 (chr. 6), were found to be linked for Ca. Three SSR markers, RM3 (chr. 6), RM400 (chr. 6) and RM286 (chr. 11) were found to be associated with Cu content. RM 311 on chr. 10 was found to beÂ associated with Fe content. P was found to be associated with three SSR markers, namely, RM536, RM234 and RM600 on chromosomes 11, 7 and 1, respectively. Some novel QTLs were also detected and implications of these results are discussed.